2011
DOI: 10.1111/j.1447-0756.2010.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of risk factors for placental abruption and placenta previa: Case‐cohort study

Abstract: The case-cohort study technique elucidated the difference in the risk factors for placental abruption and placenta previa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 36 publications
3
36
2
3
Order By: Relevance
“…Moreover, APH was identified to have a significant association with PTB. This result was in agreement previous studies which revealed that APH is associated with a high risk of PTB [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, APH was identified to have a significant association with PTB. This result was in agreement previous studies which revealed that APH is associated with a high risk of PTB [24,25].…”
Section: Discussionsupporting
confidence: 83%
“…Our study design, including the case-cohort study, was previously reported. 5 A case-cohort study is a variation of the case-control design in which the controls are drawn from the entire base population, regardless of their disease status. The subcohort was randomly selected from the entire base population and included both cases and non-cases.…”
Section: Data Source and Study Designmentioning
confidence: 99%
“…Individual data were collected from the Japan Perinatal Registry Network database 2013, which is managed by the Japan Society of Obstetrics and Gynecology. The characteristics of this database were previously reported …”
Section: Methodsmentioning
confidence: 99%